Ways of Increasing the Investment Activity of Agricultural Enterprises - Joraev Khushvaqtbek Oybek ugli (European Science Publishing, 2024)
In the article, regular improvement of legal, socio-economic, organizational and institutional conditions that ensure wide attraction of investments in agriculture. Attention is focused on the development of mechanisms for organizing, supporting, providing benefits and implementing external economic activities of agricultural subjects, including farmers and peasant farms.
Keywords: investment, asset, real investment, financial investment, agriculture, investment activity.